Factor analysis of the difficulties faced Dean's organizational strength (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the analysis of the difficulties facing the dean's organizational strength, a global analysis based on the total degree of the relationship between the Pearson correlation coefficients after its root from the point of view of the deans' assistants. ), and their number is (205) assistant dean, and the research sample was chosen in a stratified random way, as it consisted of (180) assistant dean, with a percentage of 88%. The scale consists of (20) items, and after the data collected from the respondents' answers were processed statistically using the statistical bag (SPSS),